2022
DOI: 10.3389/fgene.2022.951239
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning identification of cuproptosis and necroptosis-associated molecular subtypes to aid in prognosis assessment and immunotherapy response prediction in low-grade glioma

Abstract: Both cuproptosis and necroptosis are typical cell death processes that serve essential regulatory roles in the onset and progression of malignancies, including low-grade glioma (LGG). Nonetheless, there remains a paucity of research on cuproptosis and necroptosis-related gene (CNRG) prognostic signature in patients with LGG. We acquired patient data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) and captured CNRGs from the well-recognized literature. Firstly, we comprehensively summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…In detail, once ZBP1 is activated, RIPK3 and caspase-8 are recruited to activate the NLRP3 inflammasome, which initiates both necroptosis and pyroptosis [78][79][80]. In addition, the bioinformatics analysis reported by Miao et al also indicated that the ZBP1, both of the cuproptosis-related and necroptosis-related gene signature, functions as a risk score for prediction of the low-grade glioma patients prognosis [81]. New outcomes from the research of Wei Gao and colleagues also revealed that the administration of elesclomol to CRC cells increased Cu(II) levels in mitochondria and downregulated the Fig.…”
Section: Cross Talk Among Components Of Necroptosis Pyroptosis Ferrop...mentioning
confidence: 98%
“…In detail, once ZBP1 is activated, RIPK3 and caspase-8 are recruited to activate the NLRP3 inflammasome, which initiates both necroptosis and pyroptosis [78][79][80]. In addition, the bioinformatics analysis reported by Miao et al also indicated that the ZBP1, both of the cuproptosis-related and necroptosis-related gene signature, functions as a risk score for prediction of the low-grade glioma patients prognosis [81]. New outcomes from the research of Wei Gao and colleagues also revealed that the administration of elesclomol to CRC cells increased Cu(II) levels in mitochondria and downregulated the Fig.…”
Section: Cross Talk Among Components Of Necroptosis Pyroptosis Ferrop...mentioning
confidence: 98%
“…By locating distinct genetic biomarkers of CAD using the LASSO technique, which were compared by the average misjudgment rates of their 10-fold cross-validations, models of DE-IRGs between CAD patients and normal samples were created (22). A SVM-RFE model was created at the same time using the "SVM" package, and its average false positive rate was also compared using a 10-fold cross-validation (23). To create OFGs for CAD, genes from both algorithms were overlapped.…”
Section: Identifying Cad-related Ofgsmentioning
confidence: 99%
“…This work constructed a novel prognostic model using a LASSO analysis, and it included six PRGs, namely CASP4, CASP5, CASP9, GSDMC, PLCG1, and IL18. Recent studies have shown that genes related to cuproptosis [ 32 , 33 ] and ferroptosis [ 34 , 35 ] are predictive of the prognosis of LGG patients, and corresponding prognostic models have been constructed. Compared with them, our model has good 1-, 3-, 5- year AUC values ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Figure S1: Cox proportional hazards (PH) test before constructing the nomogram; Table S1: Comparison of AUC values of different prognostic models based on TCGA-LGG data. References [ 32 , 33 , 34 , 35 ] are cited in Supplementary Materials…”
mentioning
confidence: 99%